STUDI TENTANG KRIYA KERAMIK PADA SANGGAR KACHIO DI GALOGANDANG ANDALEH BAWAH KECAMATAN LUHAK KABUPATEN LIMA PULUH KOTA - RAHMI NUR AZIAN, Drs. Suib Awrus, M.Pd., Dra. Jupriani, M.Sn. (Serupa The Journal of Art Education, 2016)
The study aims to (1) describe the forms of the resulting ceramic craft in studio Kachio, (2) Describe the technique of forming a ceramic craft in studio Kachio, (3) Describe the process of burning the ceramic craft which is made in studio Kachio. The method is a qualitative research with descriptive approach. The data used are primary, secondary, and collected data literature study through observation, interviews, and documentation. The study found the form of ceramics produced in studio Kachio is basically a three-dimensional works with a unique shape. All products have its own characteristics in his work. Manufacture of ceramic works in Galogandang, using the turntable media. The technique used is coil, by rolling up the clay, worm-shaped, then arrange them neatly to a ceramic form, then flattened. The combustion process in studio Kachio, use a furnace that can be used at any time either to burn in large quantities or units, they are tools and materials such as drums, bricks, straw and chaff.Keywords: Kriya ceramics, shape, mechanical, process